Fatal pulmonary embolism update: 10 years of autopsy experience at an academic medical center. Issue 9 (30th July 2013) - Sweet, Patrick H; Armstrong, Theodore; Chen, John; Masliah, Eliezer; Witucki, Peter
Objective: To investigate the rate of death caused by pulmonary embolism (PE) and the antemortem performance in diagnosis and treatment of PE. Design: A systematic search of cases involving fatal PE via PowerPath® (Sunquest) followed by chart review. Setting: An academic medical centre located in San Diego, United States of America. Participants: Postmortem cases with pathological findings of PE. Main outcome measures: After data collection and collation, the data were subject to analysis. Results: From 2002 to 2012, PE was identified as the mechanism of death in 108 of 982 cases (11%, 95% CI 9.01–12.99%) at an institution with an average autopsy rate of 30% ± 0.07%. Excluding cases where care was withheld (by advance directive) or unavailable, 29 of 108 were eligible for antemortem treatment for PE. In 31% (nine of 29) of these cases the diagnosis of PE was considered antemortem. Only three of 29 were given thrombolytics despite only one case being contraindicated. Conclusion: The rate of PE-related death is consistent with most other autopsy series and major epidemiologic studies despite advances in system wide deep venous thrombosis prophylaxis. The results validate previous studies that this diagnosis is often missed but probably improving compared to historical standards. Even when the diagnosis is considered, however, thrombolytics are not routinely given, even without contraindications. The cause of this failure to treat may require further study with comparison to patients that were treated to determine the utilization of this treatment. It also underscores the continued difficulty in the diagnosis of this disease.